Manufaktur Panci SS304 Diameter 200 mm, Tinggi 150 mm, Tebal 1 mm, Kapasitas 24 Biji/Jam - Hafizh Putra Pribadi; Syamsul Hadi; Maykhal Arifuddin Azhar; Galih Widhi Susanto; Faris Adi Pratama (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
Rusting of cookware that has the potential to contaminate food that becomes unhealthy is a problem in cooking. The manufacturing objective is to obtain a 200 mm diameter, 150 mm height, 1 mm thickness SS304 pan. The manufacturing method includes: design of a pan measuring 200 mm diameter, 150 mm height, 1 mm thickness; making punches and dies for forming the pan; making punches and dies for forming the pan lid; cutting 1 mm thick SS304 material with a diameter of 400 mm for the pan; deep drawing for forming the pan; cutting 1 mm thick SS304 material with a diameter of 237 mm for the pan lid; deep drawing for forming the pan lid; making the pan lid handle; installing the pan lid handle with bolts and nuts; trimming the pan and its lid; making a pair of pan handles; installing a pair of pan handles with rivets; finishing the pan and its lid; and checking the quality-dimensions of the pan and its lid. The manufacturing results are in the form of an SS304 pan with a diameter of 200 mm, a height of 150 mm, a thickness of 1 mm along with a pair of handles and a lid along with its handle with a total production cost of IDR 126,700/unit, and a process duration of 2.5 minutes/unit which implies that the pan can be used to cook food with a total volume including liquid of 4 liters and is able to cook up to boiling water temperature.